The Effect of Interval Squat Thrust Training and Circuit Training Against Swimming Speed of 50 Meters Breastsroke - Iqbal Risman; Adnan Fardi (Performa, 2019)
Ability of swimming 50 meters breaststroke swimming subjects specializing in FIK UNP coaching is the background of research problems. This study aims to determine the effect of interval squat thrust training and circuit training exercises on swimming speed of 50 meters breaststroke. Type of experimental research, two groups pretest-posttest. The population of swimming students specializing in FIK UNP training is 26 people, 21 men and 5 women. Sampling was done by purposive sampling technique, which is 18 men. Data collection by carrying out the initial test and final test swimming speed of 50 meters breaststroke. The data analysis technique uses the mean different test formula (t test) significant level α = 0.05. From the analysis of the data the results are obtained: there is a significant effect of interval squat thrust training on swimming speed of 50 meters breaststroke (12.94 th> tb.86) from mean 62.32 to 58.99 seconds. There is a significant effect of circuit training exercises on swimming speed of 50 meters breaststroke (11.03 th> 1.86) from mean 63.96 to 59.61 seconds. There was no significant difference between squat thrust training at intervals with circuit training with swimming speed of 50 meters breaststroke (th 0.1206 <tb 1.86).